Green Loans Program : Department of the Environment, Water, Heritage and the Arts ; Department of Climate Change and Energy Efficiency - Australian National Audit Office; Caine, Grant (Canberra, A.C.T. : Australian National Audit Office, 2010)
"The objective of the audit was to examine key aspects of the establishment and administration of the Green Loans program by DEWHA and the program's transition to DCCEE. "--p. 16.
"Audit team: Grant Caine, Brendan Mason, Joe Keshina, Christina Bagot, Jennifer Eddie, Patrick O'Neill, Barbara Cass" -- P. 4.
Includes bibliographical references and index.
Also available online
Keywords: Australia. -- Department of the Environment, Water, Heritage and the Arts -- Auditing; Australia. -- Department of Climate Change and Energy Efficiency -- Auditing; Climatic changes -- Government policy -- Australia; Renewable energy sources -- Australia